Thermoplastic-Thermosetting Merged Polyimides Derived from Furan-Maleimide - Patel, Yogesh S.; Patel, Hasmukh S. (Journal of Research Updates in Polymer Science, 2013)
Novel thermoplastic-thermosetting merged polyimide system has been developed via Diels-Alder intermolecular reaction of bisfuran A namely, 2,5-bis(furan-2-ylmethyl carbamoyl)terephthalic acid with a series of bismaleimides B1-3 containing aliphatic chain in the backbone. The intermediate Furan - maleimide Diels-Alder adducts C1-3 were aromatized and imidized (i.e. cyclized) through carboxylic and amide groups to afford thermoplastic-thermosetting merged polyimides D1-3. Synthesized polyimides were characterized by elemental analysis, spectral features, number average molecular weight (Mn) and thermal analysis. Bulk polymerization was also carried out. Proof of structures was based mainly on a comparison of infrared spectra of polyimides with those of the corresponding model compound 4 prepared from 2-(furan-2-ylmethylcarbamoyl) benzoic acid in the similar way. FTIR spectral features of polyimides D1-3 were quite identical with the model compound 4. The ‘in situ’ void - free glass fiber reinforced composites GFRC1-3 were prepared and characterized by mechanical, electrical and chemical properties. The ‘in situ’ produced polyimides show good adhesion to glass fibers. All the composites depicted good mechanical and electrical properties and good resistance to organic solvents and mineral acids.